Improving the relational space of curriculum realisation social network interventions - Sinnema, Claire; Daly, Alan J.; Rodway, Joelle; Hannah, Darren; Cann, Rachel; Liou, Yi-Hwa (Emerald Publishing, 2023)
In educational policy, research and practice circles, there has been much attention in recent times to the power and potential of social networks for supporting educational improvement. Improving the Relational Space of Curriculum Realisation foregrounds the potential of the relational space, and its improvement, in the context of curriculum realisation in particular. Curriculum reform is a key lever in systems'; efforts to meet ambitious goals for student achievement, progress and wellbeing. Both large-scale reform and school-level curriculum change present learning demands for school leaders and teachers alike, and they simultaneously give rise to challenges and opportunities for those charged with giving effect to them. The authors highlight the role of social capital in addressing those demands, challenges, and opportunities, emphasising the need to improve the relational space within which curriculum change takes place. Improving the Relational Space of Curriculum Realisation outlines an approach to intervention that helps educators solve problematic patterns in their networks, leverage resources better within and across school networks, and embed relational conditions that are conducive to ambitious curriculum goals being realised.
Includes bibliographical references and index. - Print version record
Keywords: Curriculum change / Social aspects; Educational change / Social aspects; Educational innovations / Social aspects; Social networks; Education; Curricula; Curriculum planning & development